Comparison of Perianal Swab and Stool Samples for Detection of Gastrointestinal Colonization with Ceftriaxone-Resistant and Fluoroquinolone-Resistant Enterobacteriaceae. (4th October 2017) - Satlin, Michael; Hovan, Michael; Westblade, Lars; Calfee, David P; Walsh, Thomas J; Kreiswirth, Barry N; Jenkins, Stephen G
Abstract: Background: Stool samples are the gold standard for detecting gastrointestinal colonization with multidrug-resistant Enterobacteriaceae (MDR-E), but they cannot be rapidly collected. Perianal swabs can be efficiently collected and are considered safe in neutropenic patients, but there are sparse data comparing their performance characteristics to those of stool samples for detecting colonization with MDR-E. Methods: Stool and perianal swab samples (ESwab™) were collected as part of a prospective study of patients with acute leukemia and hematopoietic stem cell transplant recipients. We analyzed perianal swab and stool samples that were collected from subjects simultaneously, defined as within one day of each other. One-hundred microliters of vortexed Amies liquid from the swab and 1 μL of stool were directly plated onto chromogenic ESBL agar and MacConkey agar with 1 μg/mL ciprofloxacin (Mac-Cipro), and these plates were incubated for 48 and 24 hours, respectively. Colonies isolated on these plates were identified by MALDI-TOF mass spectrometry and underwent antimicrobial susceptibility testing. We then compared the yield of stool and swab samples for detection of ceftriaxone-resistant (CRO-R-E) and fluoroquinolone-resistant (FQ-R-E) Enterobacteriaceae. Results: A total of 108 patients had 122 perianal swab and stool samples collected simultaneously and had these samples plated onto ESBL agar. Twenty-one of these paired samples yielded CRO-R-E from either sample, including 17 cases where CRO-R-E were detected from the perianal swab (81% sensitivity) and 18 cases where CRO-R-E were detected from stool (86% sensitivity). The most common CRO-R-E were Escherichia coli ( n = 13), Klebsiella pneumoniae ( n = 5), and Citrobacter freundii ( n = 3). Sixty paired perianal swab and stool samples were also plated onto Mac-Cipro agar and 21 yielded FQ-R-E in either sample. The perianal swab sample was positive in all 21 cases (100% sensitivity) and the stool samples were positive in 20 of these cases (95% sensitivity). All FQ-R-E were E. coli ( n = 18) or K. pneumoniae ( n =  5). Conclusion: Perianal swabs have comparable performance characteristics to stool samples for detection of CRO-R-E and FQ-R-E, and thus may be employed to rapidly and safely detect gastrointestinal colonization with MDR-E on an inpatient unit. Disclosures: M. Satlin, Hardy Diagnostics: Investigator, Research support;   T. J. Walsh, The Medicines Company: Consultant and Investigator, Consulting fee and Research grant; Astellas: Consultant and Investigator, Consulting fee and Research grant; Allergan: Consultant and Investigator, Consulting fee and Research grant; Merck: Consultant and Investigator, Consulting fee and Research grant; S. G. Jenkins, Cormedix: Consultant, Consulting fee; Bayer: Consultant, Consulting fee; Merck: Grant Investigator and Scientific Advisor, Research grant